Application Mechanisms of Sales Tax in the GCC Countries: An Empirical Study on the Kingdom of Bahrain - qalbein, Ahmed Mohammed Abu (International Journal of Psychosocial Rehabilitation, 2020)
The Gulf Co-operation Council (GCC) countries (i.e. Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates) enjoy one of the least demanding tax systems in the world. The average total tax rate for the entire Middle East region is 23.6 percent, which is much less than the global average of 44.7 percent. Thus, the taxation structure and system of the GCC nations is uncomplicated when compared to rest of the world. Moreover, the GCC nations depend heavily on indirect taxes and revenue from energy exports, rather than internally generated funds. Though this system has its advantages, it may become a cause of concern for authorities in the future as taxation can influence the overall growth in different dimensions. Thus this study analysed the effect of sales tax collection on the economic development in Bahrain. To do so, a structured survey was conducted for receiving observations of 384 tax payee respondents in Bahrain and to analyse the effect. The data is analysed and hypothesis is tested by using IBM-SPSS-AMOS package 25.0. The study found that the direct effects of sales tax on the economic development in Bahrain are positive and significant. The originality of the manuscript goes back to studying the concept in the Arab world. On the basis of the result, this research endorsed that, the economic development in Bahrain is heavily in line with consistent growth of revenue collection efficiency.